Assesment of Early Children's Development Based on Child Brain Development (POA) at PAUD Terpadu Mutiara Yogyakarta - HIbana (International Conferences on Early Childhood Education Proceedings, 2023)
Many Early Childhood Education Institutions hope that their students can grow and develop optimally. The importance of assessment in aspects of child development is one of the things that must be considered, especially the assessment of early childhood development based on child brain development (POA). Because through POA-based assessment, children's developmental background can be traced. Assessment of this aspect of development becomes the basis for further development of the child. This research was conducted at PAUD Terpadu Mutiara. The use of POA activity feeds in Mutiara integrated ECCE provides information to educators and parents, so that parents can participate in providing assistance and supporting the achievement of optimal child growth and development. In this study, an assessment was carried out, especially motor aspects, which underlie the development of other aspects. Based on this research, research can understand how important the assessment is carried out so that the advantages and disadvantages of children are known in the process of growth and development. This study used qualitative research methods by collecting data through observation and interviews. Judging from the results of data analysis through observation and interviews as a whole, the implementation of the assessment in PAUD Terpadu Mutiara Yogyakarta showed that most children had no interference in carrying out activity feeds, meaning that they had been able to achieve developmental tasks well, reaching 68%. Some children who experience slight interference in doing bait activity, which is 17%. The number of children who experience enough disorders is 11%, and those who experience many disorders there are 4%. No child fails to do activity bait. The role of parents and teachers is very significant in supporting the achievement of developmental tasks. From the results of this study it can also be understood that child development assessment is needed in an institution to understand the level of child development.